Prevalence Of Three Rooted Primary Mandibular Molars In Children Visiting A University Hospital In Chennai - A Retrospective Study - BALAJI, KEERTHANA; MANI, GEO; D, PRADEEP (The journal of contemporary issues in business and government, 2021)
Awareness and knowledge of the presence of accessory roots and variation in the root canal morphology in primary mandibular molars are essential to determine the positive outcome of the treatment. In this study, we aimed to evaluate the presence of three rooted primary mandibular molars in children of Chennai population.This study was designed as a retrospective study, conducted among patients who reported to the University dental hospital.Subjects aged 2 to 10 years of chennai population, subjects who underwent endodontic procedures with complete data were included in this study. Subjects of other regions were excluded from this study.Data was collected and tabulated in excel. Data was analysed using IBM SPSS Statistical Analyzer(23.0 version).Frequency distribution and descriptive analysis were carried out. The association between the variables was analysed and assessed using Pearson Chi-square test.p value < 0.05 was considered to be statistically significant.The total occurrence of there rooted primary mandibular molars among the study subjects was found to be 0.8% among different age as well as gender.Prevalence of three rooted primary mandibular molars was found to be higher in males compared to females among the study population.